2017
DOI: 10.18203/2320-6012.ijrms20170024
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in epilepsy

Abstract: Background: The quality of life (QOL) evaluation is a relatively new measure to evaluate the outcome of epilepsy. Many factors influence the quality of life of people with epilepsy, including seizure severity, stigma, fear, and the presence of cognitive or psychiatric problems. QOL is influenced by biological factors as well as cultural, social and religious beliefs and values. This study was planned to find out the impact of epilepsy on quality of life of epileptic patients.Methods: The study was conducted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 6 publications
3
8
0
Order By: Relevance
“…ose who are unemployed get bored and face more cognitive problems. is nding is similar to the study done by Singh and Pandey [31] and Ashjazadeh et al [32]. Mean QOLIE-10 score of patients with household monthly income <22 USD was 21.4. e score is signi cantly higher (lower quality of life) than for patients who got 22 USD or more per month.…”
Section: Ethical Approvalsupporting
confidence: 90%
See 2 more Smart Citations
“…ose who are unemployed get bored and face more cognitive problems. is nding is similar to the study done by Singh and Pandey [31] and Ashjazadeh et al [32]. Mean QOLIE-10 score of patients with household monthly income <22 USD was 21.4. e score is signi cantly higher (lower quality of life) than for patients who got 22 USD or more per month.…”
Section: Ethical Approvalsupporting
confidence: 90%
“…Patients who perceive their epilepsy status was controlled had better quality of life as had no formal education. is nding is supported by many other studies [16,[29][30][31]. e poor QoL observed in illiterate patients may be due to the lesser knowledge they may have about the diseases and its treatment; as well as they may not easily understand instructions given from health professionals and this may result in poor adherence to medication and poorer seizure control which may nally lead to poor quality of life.…”
Section: Factors Associated With Quality Of Lifementioning
confidence: 72%
See 1 more Smart Citation
“…This is in line with the results of various studies Marital status had a significant influence on all domains of QoL in the present study. These findings were consistent with the results of the study conducted by Singh et al (14) which showed that the mean QOLIE-9 total scores were 16.66, 19.74, 20.13, and 24.00 in married, widowed, unmarried, and separated individuals, respectively. The differences in the means were statistically significant in ANOVA (p=0.002).…”
Section: Discussionsupporting
confidence: 93%
“…The differences in the means were statistically significant in ANOVA (p=0.002). This implies that marriage confers a benefit to QoL (14). The marital relationship is an important constituent of family and provides social support and satisfaction, and failure to maintain marriage goes against social norms.…”
Section: Discussionmentioning
confidence: 99%